1989
DOI: 10.1055/s-2006-962095
|View full text |Cite
|
Sign up to set email alerts
|

New Cucurbitacin Glycosides fromPicrorhiza kurrooa

Abstract: From the roots of Picrorhiza kurrooa Royle and Benth., seven cucurbitacin glycosides have been isolated and structurally elucidated mainly by NMR and mass spectroscopy. Four of them (4, 5, 6, 7) are new and two, the 2-O-glycoside of cucurbitacin B (25-acetoxy-2-beta-glucosyloxy-16,20-dihydroxy-9-methyl-19-norl anosta-5, 23-diene-3,11,22-trione) and the 2-O-glucoside of 23,24 didydrocucurbitacin B (25-acetoxy-2-beta-glucosyloxy-16,20-dihydroxy-9-methyl-19-norl anost-5-ene-3, 11-22-trione) were so far not report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 5 publications
(5 reference statements)
1
31
0
1
Order By: Relevance
“…3), indicated that these four CO groups belonged to the isochebulic or chebulic acid moiety. Other correlations were observed between the CO signals at d C 167.5 and 165. and 165.5 ppm, respectively, and indicated that the HHBP moiety was connected to C(4) and C (6). Similarly, the galloyl residue at C(1) and the isochebulic or chebulic acid moiety at C(2) and C(4) were evident from HMBC correlations (Fig.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…3), indicated that these four CO groups belonged to the isochebulic or chebulic acid moiety. Other correlations were observed between the CO signals at d C 167.5 and 165. and 165.5 ppm, respectively, and indicated that the HHBP moiety was connected to C(4) and C (6). Similarly, the galloyl residue at C(1) and the isochebulic or chebulic acid moiety at C(2) and C(4) were evident from HMBC correlations (Fig.…”
mentioning
confidence: 81%
“…7.04 ppm was assigned to HÀC (6). The signals at d H 2.87 and 2.36 were correlated to the signal at d C 35.2.…”
mentioning
confidence: 93%
“…Other constituents are obtained from the dried root and rhizome. [67] The medicinal importance of PK is due to its pharmacological properties such as hepatoprotective,[8] antioxidant (particularly in liver),[9] antiallergic and antiasthmatic,[10] anticancer activity particularly in liver,[11] and immunomodulatory. [12] A hepatoprotective drug formulation, picroliv, has been prepared from the extracts of PK.…”
Section: Introductionmentioning
confidence: 99%
“…During our systematic chemical investigation, two new iridoid glucosides, piscrosides A (1) and B (2), were isolated from the stems of P. scrophulariiflora, together with nine known iridoid glucosides, picroside I (3), picroside II (4), picroside III (5), picroside IV (6), 6-O-trans-feruloylcatalpol (7), minecoside (8), verminoside (9), catalposide (10), and aucubin (11) [11,12] ( figure 1). Additionally, the stems of the plant afforded only three cucurbitacin glucosides, 2b-glucopyranosyloxy-3,16,20,22-tetrahydroxy-9-methyl-19-norlanosta-5,24-diene (12) [13], 2b-glucopyranosyloxy-3,16,20,22-tetrahydroxy-19-norlanosta-5,23-diene-22-ol (13) [14], and 25-aceloxy-2b-glucopyranosyloxy-3,16,20-trihydroxy-19-norlanosta-5,23-diene-22-ol (14) [14]. The known compounds were identified by comparisons of spectroscopic data with those of reported ones.…”
Section: Introductionmentioning
confidence: 99%